Highly efficient photoanodes based on cascade structural semiconductors of Cu2Se/CdSe/TiO2: a multifaceted approach to achieving microstructural and compositional control - Chong, Baohe; Zhu, Wen; Liu, Yong; Guan, Li; Chen, George Z. (Royal Society of Chemistry, 2016)
Hydrogen produced by splitting water is receiving significant attention due to the rising global energy demand and growing climate concerns. The photocatalytic decomposition of water converts solar energy into clean hydrogen, and may help mitigate the crisis of fossil fuel depletion. However, the photocatalytic hydrogen production remains challenging to obtain high and stable photoconversion efficiency. Here, we report a highly efficient photoanode based on the coaxial heterogeneous cascade structure of Cu2Se/CdSe/TiO2 synthesized via a simple room-temperature and low-cost electrochemical deposition method. The microstructure and composition of the Cu2Se top layer are regulated and controlled by doping Cu with various amounts in different zones of the CdSe/TiO2 coaxial heterojunction and then using a simple integral annealing process. Surprisingly, a little effort made to achieve the Cu2Se top layer utilizing such doped CdSe/TiO2 exhibits a significant enhancement in photocatalytic activity. The maximum stable photocurrent density of the sample with the optimal copper zone and doping concentration has reached up to 28 mA cm−2, which can be attributed to the success in the uniform dispersion of the three-layer heterogeneous nanojunctions among the anatase nanotube wall from the top to the bottom. This results in a stepwise structure of band-edge levels in the Cu2Se/CdSe/TiO2 photoelectrode that is conducive to enhancing effectively the separation of the photogenerated electron–hole pairs.